Go-Digital Adaptation and Transformational Leadership in MSME Competitive Strategies that Impact Performance - Nainggolan, Lora Ekana; Nainggolan, Nana Triapnita; Lie, Darwin (Journal of Posthumanism, 2025)
Lake Toba tourism is one of the five super-priority destinations. Lake Toba has a very rich creative economic potential and this product must be developed to complement the tourism potential in the Lake Toba. Lake Toba tourism can compete with other tourist areas by taking advantage of the development of digitalization. Go-digitalization can also increase opportunities for business actors to develop markets that will affect economic revival and the creation of sustainable businesses. The role of HR in optimizing business performance is also important in today’s transformational era. This research was conducted with the aim of how tourism sector business actors in the Lake Toba area can apply go-digital to their businesses and how business actors understand transformational as a competitive strategy so that business performance will also increase. The research method uses field research, and the primary source of data is questionnaires. The sample in this study comprised 150 respondents, namely businesses in the tourism sector. The results of this study show that go-digital technology contributes to competitive strategies and has a significant influence on business performance.